The Usage of Time Reverse Technology to Improve The BER Performance and Transmission Rate of IR-UWB System - Alkhaddour, Mohammad; Youssef, Mazen (Al-Nahrain Journal for Engineering Sciences, 2019)
Ultra-Wideband (UWB) technology has so many striking characteristics which includes low sensitivity to fading, superior performance, low interference, easy to penetrate in walls as well as in floor. The main motive of this work is to analyze the capability of UWB technology as various aspects and improve its performance, since the main drawback of this system is that the power spectral density of the transmitted signal is rather limited. The MIMO technology may provide a solution by increasing the received SNR for the same transmission power, but the problem in this case is the spatial correlation resulted. To solve the problem two technologies are integrated along with the UWB using Time Reverse (TR) by TR-MIMO and TR-SIMO. Among these integrations, the robust performance of the UWB is analyzed by comparing the transmission rates for a given outage probability. In the last step, the (SIMO/MIMO)-UWB and TR-(SIMO/MIMO)-UWB were compared in terms of BER values to create the way of applying the UWB in so many applications.